Remote Islands as Fictional and Metaphorical Places in Cervantes, Fletcher and Shakespeare - José Manuel González (Multicultural Shakespeare, 2017)
Islands have always occupied a significant place in literature and have been a source of inspiration for the literary imagination. Fictional islands have existed as either lost paradises, or places where law breaks down under physical hardships and a sense of entrapment and oppression. Islands can be sites of exotic fascination, of cultural exchange and of great social and political upheaval. However, they are more than mere locations since to be in a place implies being bound to that place and appropriating it. That means that the islands narrow boundaries, surrounded by the sea and cut off from mainland, can create bridges between the real and the imaginary as a response to cultural and social anxieties, frequently taking the form of eutopias/dystopias, Edens, Arcadias, Baratarias, metatexts, or cultural crossroads, deeply transforming that particular geographical location. This article is concerned with insularity as a way of interrogating cultural and political practices in the early modern period by looking at the works of Cervantes, Fletcher and Shakespeare where insular relations are characterized by tensions of different sort. The arrival of Prospero and Miranda, Periandro and Auristela (The Trials of Persiles and Segismunda), and Albert and Aminta (The Sea Voyage) to their respective islands take us to a different world, revealing different political and cultural interests and generating multiple perspectives on the shifting relationship between culture, society and power.